It's a once-in-a-lifetime experience and opportunity- deal with it! volunteer perceptions of the management of the volunteer experience at the London 2012 Olympic Games - Holmes, Kirsten; Nichols, G.; Ralston, R. (Cognizant Communication Corporation, 2018)
Mega-events such as the Olympic Games involve huge numbers of volunteers from the host community, necessitating the development of a large volunteer program, which will only operate for a short time. Leveraging this volunteer energy to lead to longer-term community volunteering has become a legacy goal for many event organizers. Mega-events typically use a top-down "program management" approach for their volunteer program. This article examines how the program management style impacts on the volunteer experience, using in-depth interviews with volunteers at the London 2012 Olympic and Paralympic Games. The study found that the program management approach had a negative impact on many volunteers' preevent experience, leading to some rejecting the offer of a role at the event. However, the anticipated "once-in-a-lifetime" experience of volunteering for the Olympic Games overcame most of the preevent shortcomings. The article considers the impact of volunteer management on repeat volunteering. Recommendations for better management of mega-event volunteers, leading to a volunteer legacy, are offered.